Experience in North America Tight Oil Reserves Development. Horizontal Wells and Multistage Hydraulic Fracturing - R.R. Ibatullin (Georesursy, 2017)
The accelerated development of horizontal drilling technology in combination with the multistage hydraulic fracturing of the reservoir has expanded the geological conditions for commercial oil production from tight reservoirs in North America. Geological and physical characteristics of tight reservoirs in North America are presented, as well as a comparison of the geological and physical properties of the reservoirs of the Western Canadian Sedimentary Basin and the Volga-Ural oil and gas province, in particular, in the territory of Tatarstan. The similarity of these basins is shown in terms of formation and deposition. New drilling technologies for horizontal wells (HW) and multistage hydraulic fracturing are considered. The drilling in tight reservoirs is carried out exclusively on hydrocarbon-based muds The multi-stage fracturing technology with the use of sliding sleeves, and also slick water – a low-viscous carrier for proppant is the most effective solution for conditions similar to tight reservoirs in the Devonian formation of Tatarstan. Tax incentives which are actively used for the development of HW and multistage fracturing technologies in Canada are described. wells, multistage fracturing